Treatment of Periimplantitis with minimally invasive approach and antimicrobial photodynamic therapy - Case report. - Batista, João Pedro Oliveira de; Matos, Jefferson David Melo de; Andrade, Valdir Cabral; Morais, Tales Cyríaco; Silva, Daniela Nascimento; Martins, Sergio Henrique Lago; Vieira, Gustavo Henrique Apolinário; Ramos, Umberto Demoner (Brazilian Journal of Implantology and Health Sciences, 2025)
Periimplantitis is the most common biological complication on implant dentistry. Its prevalence is estimated of 20% of the successfully osseointegrated implants. The treatment of this complication has been a subject of great discussion in the past years. It is well accepted that non-surgical treatment has little or no effectiveness on stopping progressive bone loss and surgical treatment might be mandatory to achieve disease control. Some authors have proposed the use of Guided Bone Regeneration to regain the bone lost due to disease progression, similarly to periodontal regenerative therapies. Recently, the use of a minimally invasive surgical technique has shown promising regenerative results, without the use of biologics. The aim of this case report is to describe the use of a minimally invasive surgical technique to treat progressive bone loss around implant. A 68-year-old Caucasian female with deep pocket and infrabony defect on an implant at #14 region was treated with a minimally invasive surgical flap and decontamination with antimicrobial photodynamic therapy after removal of provisional restoration. Primary closure was achieved with 6-0 polypropylene sutures, and the healing process was uneventful, and radiographic outcomes were favorable up to 12 months. This case report shows that good regenerative outcomes can be achieved when primary closure, minimal invasiveness, and tissue stability are achieved by a surgical technique.